2010
DOI: 10.1111/j.1399-0012.2009.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous peritransplant assessment of consciousness using bispectral index monitoring for patients with fulminant hepatic failure undergoing urgent liver transplantation

Abstract: These results suggest that BIS monitoring is a non-invasive, simple, easy-to-interpret method, which is useful in assessing peritransplant state of consciousness. BIS monitoring may therefore be a useful tool during peritransplant intensive care for patients with FHF showing hepatic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
(55 reference statements)
0
7
0
4
Order By: Relevance
“…While monitoring for BIS has been developed to assess the level of awareness during anesthesia, this method may also be useful to assess the degree of recovery of con sciousness alongside improved liver function after liver transplantation. Hwang et al [9] showed that the BIS may be useful for evaluating state of consciousness during the peritransplant and intensive care periods for FHF patients who develop HE.…”
Section: Bispectral Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…While monitoring for BIS has been developed to assess the level of awareness during anesthesia, this method may also be useful to assess the degree of recovery of con sciousness alongside improved liver function after liver transplantation. Hwang et al [9] showed that the BIS may be useful for evaluating state of consciousness during the peritransplant and intensive care periods for FHF patients who develop HE.…”
Section: Bispectral Indexmentioning
confidence: 99%
“…Invasive ICP monitoring is especially risky in FHF patients with coagulopathy, for whom the incidence of intracranial bleeding due to catheter placement ranges from 5% to 22% [9,10] . Recombinant factor Ⅶ (rFⅦa) can be an alternative method for preventing intracranial hemorrh age associated with ICP placement.…”
Section: Invasive Icp Monitoringmentioning
confidence: 99%
“…A mensuração da PIC contínua no pré-operatório tem sido associada com uma taxa de sobrevivência da IHF de 54% a 74% (Hwang et al, 2010).…”
Section: Monitoração Invasiva Da Pressão Intracranianaunclassified
“…A monitoração da PIC invasiva é, geralmente, perigosa em pacientes com coagulopatia na IHF, nos quais a incidência de hemorragia intracraniana devido à colocação do cateter varia de 5% a 22% (Hwang et al, 2010;Davies et al, 1994). A utilização do rFVIIa antes da implantação do cateter de PIC parece diminuir o risco de hemorragia intracraniana (Shami et al, 2003).…”
Section: Monitoração Invasiva Da Pressão Intracranianaunclassified
See 1 more Smart Citation